Early Exposure to General Anesthesia Disturbs Mitochondrial Fission and Fusion in the Developing Rat Brain. Issue 1 (March 2015) - Boscolo, A.; Milanovic, D.; Starr, J.A.; Sanchez, V.; Oklopcic, A.; Moy, L.; Ori, C.C.; Erisir, A.; Jevtovic-Todorovic, V.
Abstract : ( Anesthesiology. 2013;118(5):1086–1097)